The Impact of Zhuangzi’s Thought on Sanmao’s Writing Style - Lin, Xuc (Bina Nusantara University, 2015)
This paper describes the impact of Zhuangzi?s thought on the San Mao?s writing style. Research was conducted by applying library research. The data for research were collected from papers, books, so on both printed and online. It is found that San Mao's writing style was divided into three stages: early stage, wanderingstage, and regression stage. These three stages are influenced by the San Mao's life changes. As a conclusion, although those three stages of writing use a completely different form, but Zhuangzi's thought influenced over her life. It also makes her always demonstrate a simple, real, and natural writing style.